Production of Dry Cakes (Cookies) Based on a Combination Between Millets Flour with Wheat - Mujianto; Tri Rahayuningsih; Endang Noerhartati; Galang Ramadhan (Jurnal Penelitian Pendidikan IPA, 2023)
The perfect diet to achieve sustainable nutrition, health, and well-being goals requires information on the quality of food sources Millet (Panicum miliaceum L.) also has an energy value comparable to that of staple cereals, and more significant health benefits due to its high fiber, minerals, vitamins, macro and micronutrients, and phytochemical compounds that are useful for chronic disorders. This research aims to analyze the production of dry cakes (Cookies) based on a combination of millet flour with wheat. This study used a Factorial Randomized Block Design with 3 (three) factors each with 2 (two) levels, repeated 2 (two) times, namely: Factors of Wheat Flour (TT), namely: TT1 = 250 gram and TT2 = 350gram, Millet flour factor (TM), namely: TM1 = 250 gram and TM2 150 gram. Refined Sugar Factor (GH): GH1 = 100 grams and GH2 = 1 gram.Â  A protein content of 8.29%, a fat content of 24.42%, a crude fiber content of 1.766%, an ash content of 1.75%, and a preference level above scale 3 (like) is obtained by optimizing the cookie-making process by replacing wheat flour with millet flour. Additionally, one gram of sucrose sugar is added.